THE DEVELOPMENT OF SHARIAH-COMPLIANT LISTED CONSTRUCTION COMPANIES INDEX (Jurnal Teknologi (Sciences & Engineering), 2016)
It is paramount to choose the appropriate index which coordinates with the composition of a particular portfolio amid examining the performance. The purpose of this study is to examine the performance of Shariah-compliant construction sector involving construction companies listed inBursaMalaysia. The objective of this study is to develop Shariah-compliant indices comprising of construction sector and other Shariah-compliant sectors inBursaMalaysiafrom 2004 to 2014. These indices are intended to be used to assist investors to compare the performance of listed construction companies (35 Shariah compliant companies as in November 2014) with other asset classes. The data collected reflects a full year annual return of the companies in the sample for the period regardless of each company’s financial year. The findings are expected to show portfolio diversification benefits of investing in Shariah-compliant listed construction companies. This will encourage more investors, locally and internationally, to invest in Shariah-compliant construction companies.